Serogroup and Clonal Characterization of Czech Invasive Neisseria meningitidis Strains Isolated from 1971 to 2015 - Jandova, Zuzana; Musilek, Martin; Vackova, Zuzana; Kozakova, Jana; Krizova, Pavla (PloS one, 2016)
BACKGROUND: This study presents antigenic and genetic characteristics of Neisseria meningitidis strains recovered from invasive meningococcal disease (IMD) in the Czech Republic in 1971-2015. MATERIAL AND METHODS: A total of 1970 isolates from IMD, referred to the National Reference Laboratory for Meningococcal Infections in 1971-2015, were studied. All isolates were identified and characterized by conventional biochemical and serological tests. Most isolates (82.5%) were characterized by multilocus sequence typing method. RESULTS: In the study period 1971-2015, the leading serogroup was B (52.4%), most often assigned to clonal complexes cc32, cc41/44, cc18, and cc269. A significant percentage of strains were of serogroup C (41.4%), with high clonal homogeneity due to hyperinvasive complex cc11, which played an important role in IMD in the Czech Republic in the mid-1990s. Serogroup Y isolates, mostly assigned to cc23, and isolates of clonally homogeneous serogroup W have also been recovered more often over the last years. CONCLUSION: The incidence of IMD and distribution of serogroups and clonal complexes of N. meningitidis in the Czech Republic varied over time, as can be seen from the long-term monitoring, including molecular surveillance data. Data from the conventional and molecular IMD surveillance are helpful in refining the antimeningococcal vaccination strategy in the Czech Republic.
Keywords: Meningococcal Infections; Multilocus Sequence Typing; séroskupina; meningokokové infekce; incidence; Humans; multilokusová sekvenční typizace; Serogroup; Neisseria meningitidis; Czech Republic; techniky typizace bakterií; Incidence; Bacterial Typing Techniques; lidé; Česká republika